2020
DOI: 10.1101/2020.02.10.942581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlating nuclear morphology and external force with combined atomic force microscopy and light sheet imaging separates roles of chromatin and lamin A/C in nuclear mechanics

Abstract: Nuclei are constantly under external stressbe it during migration through tight constrictions or compressive pressure by the actin capand the mechanical properties of nuclei govern their subsequent deformations. Both altered mechanical properties of nuclei and abnormal nuclear morphologies are hallmarks of a variety of disease states. Little work, however, has been done to link specific changes in nuclear shape to external forces. Here, we utilize a combined atomic force microscope and light sheet microscope (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 79 publications
(109 reference statements)
2
36
0
Order By: Relevance
“…To test our theory (Fig3E,F), we characterized the nuclear volume and cell density, as internal rulers for external mechanical pressure( 37 ). In asters, as expected, nuclear volume decreased towards the center (Fig.3G,H), and cell density increased (Fig.3G,I).…”
Section: Main Textmentioning
confidence: 99%
“…To test our theory (Fig3E,F), we characterized the nuclear volume and cell density, as internal rulers for external mechanical pressure( 37 ). In asters, as expected, nuclear volume decreased towards the center (Fig.3G,H), and cell density increased (Fig.3G,I).…”
Section: Main Textmentioning
confidence: 99%
“…Exact solutions to physical problems characteristic of these models typically require idealized conditions and sweeping assumptions that almost certainly do not hold true for biophysical problems. Cell nuclei have been shown to be anisotropic [ 11 ], heterogeneous [ 12 ], and strain stiffening in both compression [ 7 ] and extension [ 8 ]; this directly invalidates these key assumptions. One must then be cautious in interpreting the absolute magnitude of the mechanical properties determined by such schematic models as their assumptions are often not met.…”
Section: Classifications Of Mechanical Modelsmentioning
confidence: 99%
“…However, computationally solving CM models through means such as finite element analysis (FEA) allows investigators to circumvent some of assumptions of analytically-solved CM models at the cost of computational intensity. For example, computationally solved CM models of AFM have allowed investigators to move beyond the Hertz model and study the separate roles of lamins and chromatin, more accurate nuclear geometries, and viscous contributions [ 7 , 16 , 17 , 18 ]. The first benefit of this approach is in the flexibility of the geometry of the system.…”
Section: Classifications Of Mechanical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While quite often the nucleus is considered to be the stiffest organelle in the cell [1,[9][10][11][12], other studies have shown that the nucleus is relatively soft, at least softer than the cytoskeletal structures [6,[13][14][15]. The recent studies have established that the mechanical behavior of the nucleus is quite complex, and different properties are expected in different deformation ranges and modes [3,16,17]. The mechanical properties of the nucleus were shown to be determined by chromatin at low deformations, and by lamina (a meshwork of intermediate filaments under the nuclear envelope) at high deformations [16,17].…”
Section: Introductionmentioning
confidence: 99%